Evaluation of Comfort for Passengers of Railway Vehicles - Juraj Gerlici; Tomas Lack; Zuzana Ondrova (Communications - Scientific letters of the University of Zilina, 2007)
The passenger’s complex sensation felt during the application of oscillations and/or inertia forces, via the whole-body transmission is defined and evaluated with the help of comfort indexes such as a mean comfort; mean permanent sensation evaluated according to the measurement procedures for the indexes, and comfort on curve transition, discomfort due to a perceived curve entry or reverse transmission, or comfort on discrete events - discomfort, due to a perceived transient oscillation on a straight track, curves and curve transitions. In the text the authors deal with mean comfort evaluation and its qualification with the help of the Comfort Indexes.